2022
DOI: 10.3390/biology11040536
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antiviral T-Cell Responses by Vitamin C Suggests New Strategies to Improve Manufacturing of Virus-Specific T Cells for Adoptive Immunotherapy

Abstract: Allogeneic and autologous transplantation of hematopoietic stem cells (HSCT) are being routinely used to treat patients with leukemia and lymphoma. Due to the required immunosuppression after stem cell transplantation, infection and reactivation by viruses are life-threatening complications. In recent years, adoptive transfer using virus-specific T cells (VSTs) has emerged as alternative to conventional therapies. Since vitamins are described to influence the immune system and its cellular components, the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The antioxidant property of vitamin C also relies on the reduction of ROS-mediated expression of proinflammatory cytokines including interleukin (IL)- 1 and tumor necrosis factor alpha (TNFα) by inhibiting nuclear factor kappa B (NF-kB) transcription [ 25 ]. The impact of ascorbic acid on T cells has also been verified through reports, suggesting that it strengthens antioxidant-mediated immunity and enhances the antigen-specific response of T cells, indicating the potential of vitamin C for altering immune responses [ 26 , 27 ]. Notably, a suboptimal reduction in antioxidants can impair immunosuppression by inducing T cell apoptosis.…”
Section: Overview On Impact Of Vitamin C On Innate and Adaptive Immun...mentioning
confidence: 98%
“…The antioxidant property of vitamin C also relies on the reduction of ROS-mediated expression of proinflammatory cytokines including interleukin (IL)- 1 and tumor necrosis factor alpha (TNFα) by inhibiting nuclear factor kappa B (NF-kB) transcription [ 25 ]. The impact of ascorbic acid on T cells has also been verified through reports, suggesting that it strengthens antioxidant-mediated immunity and enhances the antigen-specific response of T cells, indicating the potential of vitamin C for altering immune responses [ 26 , 27 ]. Notably, a suboptimal reduction in antioxidants can impair immunosuppression by inducing T cell apoptosis.…”
Section: Overview On Impact Of Vitamin C On Innate and Adaptive Immun...mentioning
confidence: 98%
“…Spermidine supplementation in hepatitis B virus (HBV)-vaccinated mice also improves Ag-specific CD8 T-cell protection [ 134 ]. Similarly, another recent study showed that cytomegalovirus (CMV)-specific T-cell functionality can be improved by vitamin C pre-treatment for several days [ 135 ]. Altogether, data show that while many approaches to stimulate autophagy with drugs and/or dietary supplementations, such as rapamycin, spermidine, niacin, and metformin, have shown promise in preclinical studies, their translation to HIV-1-related clinical application and their overall efficacy and safety profiles in PLWH require further investigations.…”
Section: Therapeutic Tools To Induce Autophagy In T-cells Of Plwhmentioning
confidence: 99%
“…In general, VitC was found to preferentially drive T cells into the Th1 differentiation pathway [37, 38]. However, VitC also enhances the growth and effector activity of cytomegalovirus‐specific human CD8 CTL [39]. These effects are likely due to the antioxidant and epigenetic activity of VitC.…”
Section: Introductionmentioning
confidence: 99%